2012
DOI: 10.1371/journal.pone.0032263
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Is Required for the Sexually Dimorphic Effects of Repeated Binge-Pattern Alcohol Exposure on the HPA Axis during Adolescence

Abstract: Alcohol consumption during adolescence has long-term sexually dimorphic effects on anxiety behavior and mood disorders. We have previously shown that repeated binge-pattern alcohol exposure increased the expression of two critical central regulators of stress and anxiety, corticotrophin-releasing hormone (CRH) and arginine vasopressin (AVP), in adolescent male rats. By contrast, there was no effect of alcohol on these same genes in adolescent females. Therefore, we tested the hypothesis that 17β-estradiol (E2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…These BECs were about 200 mg/dl and they are comparable to the concentrations reported in other studies conducted in adolescent Wistar rats using a model of binge-like drinking with i.p. injections of 3 g/kg, which reported 150–180 mg/dl 1 h postinjection (Przybycien-Szymanska et al, 2010 , 2012 ). Although our procedure raised plasma alcohol levels in a binge-like manner [binge drinking is indeed defined as heavy episodic drinking within a BEC of 80 mg/dl or higher (NIAAA, 2004 )], the alcohol administration was injected and it is possible that our model would yield higher alcohol doses than animals would consume voluntarily as it is expected in a binge drinking pattern (Spanagel, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…These BECs were about 200 mg/dl and they are comparable to the concentrations reported in other studies conducted in adolescent Wistar rats using a model of binge-like drinking with i.p. injections of 3 g/kg, which reported 150–180 mg/dl 1 h postinjection (Przybycien-Szymanska et al, 2010 , 2012 ). Although our procedure raised plasma alcohol levels in a binge-like manner [binge drinking is indeed defined as heavy episodic drinking within a BEC of 80 mg/dl or higher (NIAAA, 2004 )], the alcohol administration was injected and it is possible that our model would yield higher alcohol doses than animals would consume voluntarily as it is expected in a binge drinking pattern (Spanagel, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is based on the fact that reproductive hormones predominately regulate the HPA axis activity in females but not in males [25]. Furthermore, one study showed that 17β-estradiol, the predominant sex steroid hormone in females, is required for the sexually dimorphic effects of repeated alcohol exposure on the HPA axis during adolescence [54]. …”
Section: Discussionmentioning
confidence: 99%
“…This change in corticosterone response is associated with an increase in CRH gene expression in the hypothalamus of male, but not female, rats exposed repeatedly to ethanol. Subsequent studies revealed this sex difference was due to a protective effect of estradiol on ethanol-induced upregulation of gene expression in females (Przybycien-Szymanska et al, 2012). When tested during adulthood, male rats pre-exposed to ethanol during adolescence, compared to saline-treated controls, exhibit reductions in basal corticosterone levels and exaggerated increases in corticosterone and CRH gene expression following ethanol challenge (Przybycien-Szymanska et al, 2011).…”
Section: Alcohol and Adolescencementioning
confidence: 99%